Signal processing for passive bistatic radar - Malanowski, Mateusz (Artech House radar library., 2019)
Illustrated with both simulated and measured data, this cutting-edge resource introduces the basic concepts of passive bistatic radar, such as bistatic geometry, bistatic radar equation and analysis of different illuminating signals. --